Rehabilitation of pelvic floor dysfunction after radiation therapy for a rare gynecological cancer: A case report - Eileen Coughenour; Fatimah Alkhameys; Neena K. Sharma (Gynecologic Oncology Reports)
Objective: Radiation therapy (RT) for gynecological cancers has significant effects on patients’ quality of life regarding sexual dysfunction, urinary incontinence (UI), fecal incontinence (FI), and psychological distress. There is a scarcity in literature for the inclusive therapeutic approaches of pelvic health physical therapy (PHPT) for cancer survivors. Therefore, this case describes a comprehensive PHPT program to address the complexity of pelvic floor dysfunctions due to RT. Case description: A 54-year-old female was diagnosed with high-grade neuroendocrine carcinoma of the vagina. After a one-year treatment of chemotherapy and RT, the patient presented with overall fatigue, psychological distress, dyspareunia, mixed UI, fecal urgency and FI, and bilateral vulvar lymphedema. The PHPT exam revealed vaginal dryness, vulvovaginal fibrosis, and pelvic floor muscle (PFM) weakness.A comprehensive treatment approach included referrals to multidisciplinary specialists. PHPT incorporated motor learning, strengthening and stretching of PFM, internal and external fascia mobilization for PFM and vulvar tissues, lymphatic drainage, vaginal dilators, pain neuroscience education and nutrition recommendations. After seven sessions, the patient demonstrated improved PFM strength, improved psychosocial measures, no UI or FI, as well as reduced discomfort during intercourse. Conclusions: Symptoms were clinically improved with a multidisciplinary approach and comprehensive PHPT. However, considering the consistency and time required for physiological and psychological recovery for gynecological cancer survivors, it was recommended to continue the plan of care and home program developed to address the patient’s goals. Impact statement: Treatment utilized a holistic and interdisciplinary approach to address the multifactorial nature of vaginal cancer and side effects of RT. PHPT, which promptly maximized improvement, included manual therapy, exercises, education, and motivational interviewing strategies that prioritized the patient’s goals and built a nurturing clinician-patient relationship. Health care providers are strongly encouraged to refer to PHPT as interventions may significantly improve the patient’s quality of life.This case report follows the CARE Guidelines (Riley et al., 2017).